PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PEMBELAJARAN TERPADU TIPE WEBBED DI SEKOLAH DASAR - Nurul Halimah; Alwen Bentri; Elfia Sukma; Melva Zainil (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to investigate the impact of using the Problem-Based Learning (PBL) model on learning outcomes in Webbed integrated learning at elementary schools. Webbed integrated learning is an approach that integrates multiple subjects into a single learning theme, while PBL is a learning method that emphasizes real-world problem-solving within the learning context. The research employed an experimental design with a Post-test Only Control Group Design. The sample consisted of third-grade students in Gugus VI, Kuranji District, Padang City, with two groups: an experimental group comprising 20 students and a control group comprising 20 students. The experimental group implemented the PBL model in Webbed integrated learning, while the control group used conventional learning in Webbed integrated learning. Learning outcome data were obtained through written tests that covered cognitive and affective aspects of integrated learning. Data analysis was conducted using an independent t-test to compare the learning outcomes between the experimental and control groups. The results showed a significant difference in the average learning outcomes of Webbed-integrated learning using the PBL model compared to the average learning outcomes of Webbed-integrated learning using conventional learning based on the results of the independent sample t-test, which yielded a sig value of 0.00 < 0.05 and a t-value > t-table with a t-value of 5.463 and a t-table value of 2.024. Therefore, it can be concluded that the use of the PBL model has an impact on learning outcomes in Webbed integrated learning.